Positive Childhood Experiences and Insomnia: Psychological Vulnerability and Subjective Vitality as Serial Mediators - Kara, Berkan Can; Dalkilinc, Gokcen; Guven, Seda Nur; Kesimalioglu, Hatice; Satici, Seydi Ahmet (SPRINGER, 2025)
Sleep is a significant factor influencing both physical and mental health. It supports thinking, emotional regulation, and vitality. However, insomnia is still a common problem, often linked to complex factors like psychological vulnerability and early life experiences. Early childhood experiences have an impact on all aspects of individuals' lives. In particular, early childhood experiences influence individuals' mental and physical health throughout life. Therefore, it is imperative to examine the impact of early childhood experiences on insomnia, with particular attention to the mediating roles of psychological vulnerability and subjective vitality. Data were collected from a sample of 1014 Turkish adults, including 776 females and 238 males, with a mean age of 32.35 years (SD = 8.73) ranging from 18 to 61 years. According to structural equation modeling, psychological vulnerability and subjective vitality fully mediated between positive childhood experiences and insomnia. In other words, positive early childhood experiences reduce the level of psychological vulnerability; this increase in subjective vitality helps reduce the level of insomnia. Consequently, it is recommended to focus on reducing psychological vulnerability, enhancing subjective vitality and emphasize the significance of positive early childhood experiences for individual-focused and protective interventions targeting insomnia. The results of this research are expected to contribute to a better understanding of the effects of positive childhood experiences on insomnia.
Keywords: Positive childhood experiences; Insomnia; Psychological vulnerability; Subjective vitality; Serial mediation model; SEVERITY INDEX; HEALTH; DEPRESSION; RESILIENCE; VALIDATION; ANXIETY; SAMPLE; SLEEP; Psychiatry